Population structure and mixed reproductive strategies in Bipolaris maydis from single and multiple corn cultivars in Fujian Province, China - Dai, Yuli; Gan, Lin; Lan, Chengzhong; Liu, Xiaofei; Liu, Wende; Yang, Xiujuan (Frontiers in Plant Science, 2023)
Bipolaris maydis is the pathogenic microorganism of southern corn leaf blight, a persistent biotic constraint responsible for substantial yield losses of corn worldwide. In the present study, 96 isolates from six representative fields growing single and multiple sweet corn cultivars in Pingnan, Fuqing, and Jian’ou in Fujian Province, which are characterized by different geographical characteristics and cropping patterns, were genetically analyzed using inter-simple sequence repeat (ISSR) markers to assess the impact of geographical origins and corn cultivars on B. maydis population differentiation. B. maydis isolates originated from diverse regions possessed higher genetic variety than those from single and multiple sweet corn cultivars. Phylogenetic analysis showed that the isolates from single and multiple sweet corn cultivars were randomly grouped into different clusters, with those from the same location tending to form clusters. A greater genetic differentiation among different geographical populations than between those from single and multiple sweet corn cultivars was observed by pairwise comparison. Hierarchical analysis indicated that among-population variation was higher when comparatively analyzed B. maydis populations from different locations than in those from single and multiple sweet corn cultivars. In conclusion, these results suggest that geographical origin acts a more considerable role in genetic differentiation of B. maydis than corn cultivar. Two divided genetic clusters were detected in the B. maydis populations from single and multiple sweet corn cultivars at the three locations in Fujian Province, with major genetic variation being derived within populations. The high haplotypic diversity and expected mating type ratio of 1:1 in combination with significant linkage disequilibrium suggested that a mixed reproductive strategy occurs in the B. maydis population in Fujian Province. This study will enrich the information on the role that geographical origins and corn cultivars play in the population structure of the pathogen as well as the reproductive strategies in B. maydis population in Fujian Province.